2020
DOI: 10.30612/agrarian.v13i47.10316
|View full text |Cite
|
Sign up to set email alerts
|

Produção, composição bromatológica e fenológica de forrageiras estivais na Região Sul do Brasil

Abstract: O presente estudo foi conduzido com o objetivo de avaliar a produção de matéria seca (MS), composição morfológica e bromatológica de diferentes forrageiras estabelecidas durante o verão, em terras baixas da fronteira oeste do Rio Grande do Sul. No experimento 1, foram utilizadas 12 parcelas (1,36×5,00 m), para avaliar os seguintes tratamentos: 1) Milheto (MIL1; Pennisetum americanum (L) cv. BRS1501®); 2) Milheto (MIL2; Pennisetum americanum (L.) cv. Campeiro®); e 3) Capim sudão (SUD; Sorghum sudanense). No exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…OM acts as a source of nutrients, soil conditioner, and food for the soil microbiota, and these characteristics improve fertility, soil aggregation, and nutrient cycling, thus promoting better nutrition and more significant biomass accumulation by sorghum [99,100]. The productivity obtained in this study is compatible with that found even when forage sorghum is irrigated with good-quality water [101][102][103].…”
Section: Sorghum Yield and Water Use Efficiencysupporting
confidence: 82%
“…OM acts as a source of nutrients, soil conditioner, and food for the soil microbiota, and these characteristics improve fertility, soil aggregation, and nutrient cycling, thus promoting better nutrition and more significant biomass accumulation by sorghum [99,100]. The productivity obtained in this study is compatible with that found even when forage sorghum is irrigated with good-quality water [101][102][103].…”
Section: Sorghum Yield and Water Use Efficiencysupporting
confidence: 82%